Exposure of hospital healthcare workers to the novel coronavirus (SARS-CoV-2) - Razvi, Salman (Clin Med (Lond), 2020)
Healthcare workers (HCWs) are at higher risk of infection with the coronavirus disease 2019 (COVID-19) and can also amplify outbreaks within healthcare facilities if they become ill. Certain groups are known to be at higher risk of contracting severe COVID-19 infection, such as men and people from Black, Asian and minority ethnic (BAME) backgrounds. Identifying and managing HCWs who have been exposed to COVID-19 is of utmost importance in preventing healthcare transmission and protecting staff and vulnerable patients in healthcare settings. Recently, antibody testing to diagnose previous COVID-19 exposure among HCW has commenced in the UK. This provided an opportunity to assess exposure to COVID-19 among the various subgroups within the HCW community, based on their roles and ethnic background. We found that HCWs working in patient-facing roles were twice as likely to have been exposed to COVID-19 than their colleagues in non-patient-facing roles. Reassuringly, workers from BAME backgrounds had a similar risk of previous COVID-19 exposure to their white colleagues. More research is required to assess how frontline staff, especially those working in patient facing roles, can reduce their risk of exposure to COVID-19.